Atypical Plasmacyte Morphology in Primary Plasma Cell Leukemia - Kosasih, Agus Susanto; Sukartini, Ninik (Indonesian Association of Clinical Pathologist and Medical laboratory, 2025)
Plasma cell leukemia (PCL) is a scarce hematology malignancy with challenging clinical picture and dismal prognosis. The diagnostic procedure is sometimes complicated and difficult due to its scarcity. Patient was a 54-year-old male who presented with generalized weakness 2 months prior to hospital admission. He had anemia, thrombocytopenia and leukocytosis with 96% blasts. Initial peripheral blood smear showed unspecific cells that turned out to be plasmacytes. Flow cytometry showed positive for CD38, CD138, Kappa, CD43 and CD200, with conclusion of myeloma. Confirmation with serum protein electrophoresis showed gamma migrating paraprotein with 35.5% gamma Ig G, reduced albumin fraction and alpha 1 globulin. There was M-spike on gamma globulin. Serum immunofixation electrophoresis (SIFE) on the next day showed oligoclonal gammopathy (bi-clonal IgG Kappa and monoclonal Kappa light chain). Based on those results, patient was diagnosed with primary plasma cell leukemia. Diagnosis of PCL is often challenging and misleading due to the clinical features resembling multiple myeloma and unspecific morphology of plasma cell. Peripheral plasmacyte >5% with M-spike on gamma globulin in SPE and gammopathy oligoclonal in SIFE (bi-clonal IgG Kappa and monoclonal Kappa light chain) were supported the diagnosis of PCL and confirmed by the positive flow cytometry for CD38, CD138, Kappa, CD43 and CD200. Therefore, utilization of modern diagnostic procedures like flow cytometry is crucial to make the diagnosis of this rare disease